2011
DOI: 10.1002/jbm.a.33094
|View full text |Cite
|
Sign up to set email alerts
|

Understanding osteoblast responses to stiff nanotopographies through experiments and computational simulations

Abstract: An increasing number of studies have demonstrated the positive role nanotopographies can have toward promoting various cell functions. However, the relevant mechanism(s) behind this improvement in biological interactions at the cell-material interface is not well understood. For this reason, here, osteoblast (bone forming cell) functions (including adhesion, proliferation, and differentiation) on two carefully-fabricated diamond films with dramatically-different topographies were tested and modeled. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…In particular, it was found that rationally designed NCD topography and nanoscale roughness (RMS roughness typically <25 nm) could enhance both short-term (adhesion, proliferation) and long-term functions (differentiation and bone synthesis) of osteoblast compared to micron or submicron crystalline diamond (MCD) [51][52][53]. Figure 5 shows images of osteoblast adhered on NCD or MCD substrates, where significant difference in cell morphology can be seen.…”
Section: Ceramics and Non-metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it was found that rationally designed NCD topography and nanoscale roughness (RMS roughness typically <25 nm) could enhance both short-term (adhesion, proliferation) and long-term functions (differentiation and bone synthesis) of osteoblast compared to micron or submicron crystalline diamond (MCD) [51][52][53]. Figure 5 shows images of osteoblast adhered on NCD or MCD substrates, where significant difference in cell morphology can be seen.…”
Section: Ceramics and Non-metalsmentioning
confidence: 99%
“…For example, filopodia formation of human osteoblast on MCD and NCD substrates, with distinct topographies but similar surface chemistry and hydrophobicity (surface energy), has been examined [53]. Interestingly, filopodia of osteoblasts cultured on MCD films tend to converge to specific sites on the diamond surface, while radial and parallel filopodia are formed on the NCD substrate.…”
Section: Cell Filopodial Dynamics On Biomaterials Nanotopographymentioning
confidence: 99%
See 1 more Smart Citation
“…The state of the filopodia may reflect the proliferative ability of cells. 25 The filopodia of cells collected by the collagenase-USV treatment were denser than those of cells collected by the trypsin-pipetting treatment.…”
Section: B Morphology Observation Of Collected Cellsmentioning
confidence: 92%
“…1 However, this nanothick passive layer is not inert to corrosive attack when subjected to aggressive biological conditions (eg, pH variation, presence of fluorides, and surface wear). 2 The intrinsic bioinertness of Ti surfaces and its alloys usually results in poor osseointegration due to insufficient bone formation, which then increases the risk of instability after surgical procedures.…”
Section: Introductionmentioning
confidence: 99%